Public activity of contemporary Ukrainian academic religious scholars in the last five years - Horkuša, Oksana Vasylivna (Ukrai͏̈ns'ke relihijeznavstvo, 2019)
In her article the author analyzes the way in which academic scholars combine professional competence and social activity. Academic Studies of Religious is a strategic branch of the humanities, that the practical consequences of theoretical achievements contribute to the establishment of mutual understanding in the multiconfessional and polyscriptive social context. Ukrainian academic scholars jf religious are at the same time scholars as theoreticians and citizens of modern Ukraine. Therefore, they often continue their professional scientific and cognitive activities in the educational and public sector. It is ascertained that, as guided by the principle of scientific prudence and at the same time civic engagement, contemporary Ukrainian academic religious scholars influence social reality as a means of public activity. While staying with theoretical scholars, but at the same time being active citizens included in the epicenter of the reality of modern Ukraine, Ukrainian academic religious scholars seek not only to reason and express themselves, but also to act responsibly both before the scientific community and before the civil community in order to achieve positive practical consequences of their professional achievements. It is proposed to classify the social activities of academic religious scholars according to the criteria a) collective-individuality - UAR and individual action; b) target orientation - different target groups and levels from local to international; c) the sphere of social existence - education and action in different directions; d) qualitative characteristics: whether the use of professional knowledge in public activities or professional activities in favor of the community. Religious professional competence contributes to responsible public activity, creates conditions for positive influence on the development of inter-confessional relations in a multiconfessional modern Ukraine, the formation of a developed civil society in which religious actors are effective and influential actors, rather than "hostages of processes" or "factors for account". Therefore, Ukrainian academic religious scholars and their professional activities in its subject and educational orientation, and their social activities, based on their professional competence, are included in the contemporary social and civil processes involved in such.